Prognosis of Tyrosine Kinase Inhibitor Therapy for Non-Small Cell Lung Cancer - Santoso, Agus Andreas; Pratiwi, Suryanti Dwi; Sugiri, Yani Jane; Al Rasyid, Harun; Listyoko, Aditya Sri (Jurnal Respirasi, 2025)
Introduction: Non-small cell lung cancer (NSCLC) was the primary cause of death in lung cancer. Tyrosine kinase inhibitors (TKIs) were one of the management options for NSCLC. Meanwhile, serum carcinoembryonic antigen (CEA) plays a crucial role in the diagnosis and prognosis of NSCLC patients. This study aimed to determine the effectiveness of epidermal growth factor receptor (EGFR)-TKI based on progression-free survival (PFS) and overall survival (OS) in NSCLC patients with common EGFR mutations. Methods: This retrospective cohort study used a total sampling method. The serum CEA level was measured before the initial treatment. Tyrosine kinase inhibitors therapy was monitored with PFS and OS. Statistical analysis for comparing prognosis in NSCLC among TKI groups used Kruskal-Wallis, analysis of variance (ANOVA), Mann-Whitney, and Spearman’s rho tests. A significant analysis referred to a p-value of <0.05. Results: The participants were 189 patients, consisting of 106 on gefitinib, 43 on erlotinib, and 40 on afatinib. The average PFS values in the gefitinib, erlotinib, and afatinib groups were 9.9±5.25, 8.77±4.53, and 12.83±7.02 months, respectively (p=0.016). Furthermore, there were no significant OS among the gefitinib (14.91±7.61 months), erlotinib (14.54±7.64 months), and afatinib group (15.51±8.13 months, p=0.867). There was a significant correlation between CEA levels and PFS (r=0.146; p=0.046) and between CEA levels and OS (r=0.223; p=0.004). Conclusion: Although afatinib may prolong PFS compared with gefitinib and erlotinib, it did not significantly impact OS. Increased serum CEA levels before treatment significantly improved PFS and OS. However, elevated CEA levels are usually associated with a poor prognosis in NSCLC.